Innate Functions of Dendritic Cell Subsets in Cardiac Allograft Tolerance - Schroth, Samantha; Glinton, Kristofor; Luo, Xunrong; Thorp, Edward B. (Frontiers in Immunology, 2020)
Survival rates after heart transplant have significantly improved over the last decade. Nevertheless, long-term allograft viability after 10 years remains poor and the sequelae of transplant-associated immunosuppression increases morbidity. Although several studies have implicated roles for lymphocyte-mediated rejection, less is understood with respect to non-major histocompatibility, and innate immune reactivity, which influence graft viability. As immature and mature dendritic cells (DCs) engage in both Major Histocompatibility Complex (MHC)-dependent and MHC-independent immune responses, these cells are at the crossroads of therapeutic strategies that seek to achieve both allograft tolerance and suppression of innate immunity to the allograft. Here we review emerging roles of DC subsets and their molecular protagonists during allograft tolerance and allograft rejection, with a focus on cardiac transplant. New insight into emerging DC subsets in transplant will inform novel strategies for operational tolerance and amelioration of cardiac vasculopathy.